EFFECTIVENESS OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION CORSETS THERAPY ON MENSTRUAL PAIN IN ADOLESCENTS - Pratiwi, Maulinda Rizki; Marfuah, Dewi; Mutiar, Astri; Perdani, Agni Laili (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2023)
Background: Menstrual pain is pain felt in the lower abdomen during menstruation. This pain can be cramped and last for a long time, interfering with everyday activities. Treatment in adolescents given during menstrual pain can be pharmacological or non-pharmacological. One of the non-pharmacological treatments commonly used is the Transcutaneous Electrical Nerve Stimulation (TENS) corset therapy using electrical currents through the skin that serves to lower the scale of menstrual pain. This study aimed to find out the impact of Transcutaneous Electrical Nerve Stimulation Corset Therapy on Menstrual Pain in Teenagers. Methods: This research was a quantitative research using experimental Quasi Two Group Pre-Posttest design. This study conducted toward adolescents in Bandung District area, West Java with a sample of 50 respondents, the girls were divided into two groups namely intervention and control groups with 25 respondents for easy group. The intervention was carried out for 3 days with 15 minutes of therapy a day. Sampling techniques used a purposive sampling and for data compilation used the questionnaires and a checklists characteristic menstrual pain form. Results: The age of respondents were <17 years old (38%) and >17 years old (62%), they were in Senior High School (84%) and in Junior High School (16%), age of menarche <12 years old (42%) and >12 years old (58%). The Bivariat analysis on Impact of Transcutaneous Electrical Nerve Stimulation Corset Intervention Therapy toward Menstrual Pain in Adolescents using the Wilcoxon test showed p value 0.000 (significance < 0.05), and the Mann-Withney test with p value 0.000 (< 0.05) which means there was a significant difference between the intervention group and the control group, and also ANCOVA test results showed p value 0.000. Conclusion: The conclusion of the study showed that there was an effect of the Transcutaneous Electrical Nerve Stimulation Corset therapy intervention toward Menstrual Pain in adolescents. It could be reduce level menstrual pain,